User Name Remember Me? Password

 Algebra Pre-Algebra and Basic Algebra Math Forum

 May 22nd, 2015, 12:21 PM #1 Newbie   Joined: May 2015 From: Brazil Posts: 2 Thanks: 0 Need to solve for α Hello, I'm new here. It was good to find about this forum. Interested in exchanging ideas, even though I'm no math wizard. Anyway, my current problem is that I need to solve the following equation for α: p(f − 1)/(1 − α + fα) − (1 − p)/(1 − α) = 0 I already know the answer, which is α = (pf − 1)/(f-1), but I can't solve it by myself. I've tried a few different ways but can't figure out what are the steps to get to the solution. I'd be really glad if someone could help me out with this. Thanks in advance May 22nd, 2015, 02:12 PM #2 Global Moderator   Joined: Dec 2006 Posts: 20,919 Thanks: 2201 p(f − 1)/(1 − α + fα) − (1 − p)/(1 − α) = 0 (I'll assume f = 1 and p = 1 are not true.) Multiply through by (1 − α + fα)(1 − α): p(f − 1)(1 − α) − (1 − p)(1 − α + fα) = 0 Hence p(f - 1) - pα(f - 1) - (1 − p) + α(1 − p) - fα(1 − p) = 0, and so pα(f - 1) - α(1 − p) + fα(1 − p) = p(f - 1) - (1 − p) = pf - 1. Hence α = (pf - 1)/(p(f - 1) - (1 − p) + f(1 − p)) = (pf - 1)/(pf - p - 1 + p + f − fp) = (pf - 1)/(f - 1). If p = 1 or f = 1, they must both equal 1 and α can have any value except 1. Thanks from MRebel May 22nd, 2015, 02:55 PM #3 Newbie   Joined: May 2015 From: Brazil Posts: 2 Thanks: 0 Nice! Thanks May 22nd, 2015, 06:47 PM   #4
Math Team

Joined: Oct 2011
From: Ottawa Ontario, Canada

Posts: 14,597
Thanks: 1038

Quote:
 Originally Posted by MRebel p(f − 1)/(1 − α + fα) − (1 − p)/(1 − α) = 0
Another way; rearrange:
p(f − 1)/(1 − α + fα) = (1 − p)/(1 − α)
Crisscross multiplication:
1 - a + fa - p + pa - fpa = pf - p - fpa + pa
Simplify:
1 - a + fa = pf
Rearrange:
fa - a = pf - 1
wrap-up:
a(f - 1) = pf - 1
a = (pf - 1) / (f - 1) Tags solve Thread Tools Show Printable Version Email this Page Display Modes Linear Mode Switch to Hybrid Mode Switch to Threaded Mode Similar Threads Thread Thread Starter Forum Replies Last Post gen_shao Algebra 12 November 2nd, 2014 06:11 AM

 Contact - Home - Forums - Cryptocurrency Forum - Top

Copyright © 2019 My Math Forum. All rights reserved.      